Journey toward Baby-Friendly Hospital Initiative designation: Healthcare professional's view on successful implementation process and maintenance of accreditation - Mäkelä, Heli; Axelin, Anna; Niela-Vilén, Hannakaisa (Elsevier, 2025)
Problem
The Baby-Friendly Hospital Initiative has yet to achieve widespread global implementation.
Background
The implementation of the Baby-Friendly Hospital Initiative has been recognised as complex. The challenge has been to maintain accreditation.
Aim
To explore and gain a deeper understanding of the healthcare professionals’ perceptions of the implementation process and the maintenance of the Baby-Friendly Hospital Initiative.
Methods
A qualitative descriptive study with focus groups (n = 10) of the nurses, midwives and unit leaders (n = 43) perceptions of the implementation process were analysed using inductive thematic analysis.
Findings
Analysis of the data revealed five main themes: groundwork for the baby-focused breastfeeding context, management support throughout the process, promoting baby-friendly practices, effective communication ensuring the right track, and supporting the maintenance of BFHI designation. The main themes describe the implementation as a journey of climbing a hill and after reaching the top trying to maintain their position.
Discussion
The starting point for implementation was an optimal environment supporting baby-friendly breastfeeding practices. The support of the management of the organisation was an important way of moving the implementation forward. Commitment to the common goal strengthened the baby-friendly approach and with concrete and immediate feedback the right pathway on a journey was ensured.
Conclusion
Practical ways to support the implementation journey include regular update education on breastfeeding and continuous monitoring, as well as providing statistics to health professionals. Global guidelines on how to sustain change are needed. This will ensure that the work done is not wasted.